PENGENDALIAN ANTIBIOTIK BERDASAR METODE KONSUMSI ABC DENGAN PENERAPAN MINIMUM-MAXIMUM STOCK LEVEL TERHADAP EFISIENSI PERSEDIAAN FARMASI RUMAH SAKIT - yudha pranata; Agusdini Banun; Mohamad Reza Hilmy (Jurnal Health Sains, 2022)
Inefficient planning and control of drug supplies, apart from causing shortages or excess stocks, can also lead to inefficiency in hospital operating costs. This study aims to determine the effect of applying the Minimum-Maximum Stock Level (MMSL) method on the efficiency and effectiveness of drug supply in the Pharmacy Installation of RSU. Sanggau Medical Center. The sample group of class A antibiotics from the ABC consumption method as many as 22 types of drugs were taken purposively from retrospective data from January - June 2021, and applied the MMSL method prospectively in October - December 2021. Data analysis was carried out on inventory values, month-stock, and ITOR (Inventory Turn Over Ratio) before and after the application of the MMSL method using the Wilcoxon Signed Rank Test statistical test.The results of statistical tests showed the effect of applying the MMSL method to the month-stock ratio of the antibiotic group before the intervention was 2.87 and after the intervention was 2.03 with a p value of 0.021 (p <0.05). While the ITOR value before the intervention was 13.73 times/year and after the intervention was 19.16 times/year with p value = 0.006 (p<0.05). Although it did not show a significant difference in the inventory value of the antibiotic group between before the intervention (Rp. 62,497,441,) - and after the intervention (Rp. 54,072,358,-), with p value = 0.236 (p>0.05), but shows an efficiency of 13.48%. The application of the MMSL method has a positive impact on increasing the efficiency of drug control in hospitals by decreasing the inventory value and month-stock ratio, as well as increasing ITOR